2017
DOI: 10.1007/s10549-017-4123-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with the uptake of contralateral prophylactic mastectomy among BRCA1/2 mutation noncarriers with newly diagnosed breast cancer

Abstract: Purpose Women who are newly diagnosed with breast cancer may consider contralateral prophylactic mastectomy (CPM) to reduce their future risk of cancer in their unaffected breast. Pre-surgical BRCA1/2 genetic testing can provide valuable risk information to guide this choice. However, little is understood about why BRCA1/2 mutation noncarriers, who are generally not at substantially elevated risk of contralateral disease, select CPM. Methods We examined the uptake of CPM among breast cancer patients identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…Despite these findings, rates of CPM continue to increase 12,13,21‐25 . Although the reasons for this trend are under investigation, 2,5,7,21,22,26‐28 patient anxiety and overestimation of personal contralateral breast cancer risk (CBC) have received substantial attention as a driving force for the increasing utilization of CPM 4,15,21,24,27,29 . Using patient‐directed surveys, one previous study has shown that patients overestimate their risk for CBC, with 10‐year self‐reported risk estimates over 30% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, rates of CPM continue to increase 12,13,21‐25 . Although the reasons for this trend are under investigation, 2,5,7,21,22,26‐28 patient anxiety and overestimation of personal contralateral breast cancer risk (CBC) have received substantial attention as a driving force for the increasing utilization of CPM 4,15,21,24,27,29 . Using patient‐directed surveys, one previous study has shown that patients overestimate their risk for CBC, with 10‐year self‐reported risk estimates over 30% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Com as análises BRCA-1 e BRCA-2 aumentaram as indicações de mastectomia subcutânea bilateral preventiva e mastectomia contralateral profilática (CPM) 2 .…”
Section: Métodosunclassified
“…While they are not always necessary nor feasible, psychological consultations are frequently recommended and completed in order to best support decision-making, minimise potential patient regret, and assess suitability and readiness for surgery. [11][12][13][14] Literature suggests that some patients may especially benefit from presurgical assessment, including those with anxiety or other psychological distress, [12][13][14][15] a high perception of cancer risk, 15,16 decisionmaking difficulty, 15 a family member who has experienced BC, 13,15 or perception that others are endorsing patient's surgery uptake. 15,16 Studies suggest that some women may perceive a routine psychological consultation to be appropriate and helpful in consolidating their preferences and assisting with decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Literature suggests that some patients may especially benefit from presurgical assessment, including those with anxiety or other psychological distress, [12][13][14][15] a high perception of cancer risk, 15,16 decisionmaking difficulty, 15 a family member who has experienced BC, 13,15 or perception that others are endorsing patient's surgery uptake. 15,16 Studies suggest that some women may perceive a routine psychological consultation to be appropriate and helpful in consolidating their preferences and assisting with decision-making. 12,13 In such consultations, the patients' understanding of the procedure, along with its associated risks and benefits, decision-making preferences, and psychological distress (anxiety and body image), appear key areas to assess, among others.…”
Section: Introductionmentioning
confidence: 99%